Interpretasi Kontekstual Makna Qawwām Dalam Al-Qur’an QS. An-Nisa’ 34: Aplikasi Hermeneutika Abdullah Saeed - Zakiah, Ade Rosi Siti; Nurfajriyani, Nurfajriyani (UIN Sultan Syarif Kasim Riau, 2023)
The phrase